Residual Herbicides Alone and in Combinations for Fallow Weed Control - Randall S. Currie; Patrick W. Geier (Kansas Agricultural Experiment Station Research Reports, 2023)
The objective of this research was to compare various novel herbicides for efficacy in fallow. An experiment compared residual herbicides for preemergence weed control in fallow. While most herbicides provided good kochia control early on, only the treatments containing Alite 27 (isoxaflutole) controlled kochia 90% or more by 50 days after treatment. Similarly, most herbicides controlled Russian thistle 83% or more early. However, Russian thistle control declined such that only the treatments containing Alite 27 provided as much as 74% control later in the season.
Keywords: Herbicide-resistance; preemergence control; fallow; kochia; thistle